Zinc incorporated nano hydroxyapatite: A novel bone graft used for regeneration of intrabony defects - Vasundhra Ajay Bhardwaj; P C Deepika; Siddaramaiah Basavarajaiah (Wolters Kluwer Medknow Publications, 2018)
Background: To enhance the bioactivity of hydroxyapatite (HA), various ions have been incorporated into its porous structure such as zinc. Zinc has shown to have a stimulatory effect on osteoblastic cells. This study attempts to evaluate the efficacy of an indigenously prepared zinc incorporated nanohydroxyapatite (ZINH) bone graft in the treatment of intrabony defects. Materials and Methods: A split-mouth study, which consists of 11 systemically healthy subjects with 45 sites, were randomly treated with ZINH or with nanoHA alone. Plaque index, gingival index, gingival bleeding index, pocket depth (PD) and clinical attachment level (CAL) were assessed at baseline, 3, 6, 9, and 12 months. Bone probing depth (BPD) and radiographic parameters were assessed at baseline, 6, and 12 months. Statistical analysis used was student's t-test and one-way analysis of variance. Results: At 12 months, PD and BPD reduction was more in test (4.37 ± 0.989 mm and 3.36 ± 0.446 mm) than control (2.81 ± 0.084 mm and 2.15 ± 0.159 mm). Gain in CAL for test (3.08 ± 0.148 mm) was higher than control (2.33 ± 0.278 mm). Furthermore amount and percentage of bone fill was higher in test (1.92 ± 0.702 mm, 54.7 ± 20.286, respectively) than control (1.38 ± 0.650 mm, 40.2 ± 20.972, respectively). Statistically significant improvements in all parameters were seen in the test sites at 12 months. Conclusion: ZINH bone graft can be considered as a prospective bone regenerative material.